2015
DOI: 10.1155/2015/972891
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Organelle Stresses in Diabetes Mellitus and Obesity: Implication for Treatment

Abstract: The type 2 diabetes pandemic in recent decades is a huge global health threat. This pandemic is primarily attributed to the surplus of nutrients and the increased prevalence of obesity worldwide. In contrast, calorie restriction and weight reduction can drastically prevent type 2 diabetes, indicating a central role of nutrient excess in the development of diabetes. Recently, the molecular links between excessive nutrients, organelle stress, and development of metabolic disease have been extensively studied. Sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 135 publications
1
13
0
Order By: Relevance
“…Interestingly, it has recently been shown that autophagy negatively regulates inflammasome activation (reviewed in Pedraza‐Alva, Perez‐Martinez, Valdez‐Hernandez, Meza‐Sosa, & Ando‐Kuri, ), supporting previous observations indicating an inverse correlation between autophagy and inflammation in different pathological settings, affecting peripheral organs (Bianco, Girardelli, & Tommasini, ; Chang, Hee, Hsieh, Jeng, & Chuang, ; Lapaquette, Guzzo, Bretillon, & Bringer, ). Although, François et al, () reported that in the APPswe/PS1dE9 transgenic mice, inflammation could induce autophagy in older mice (François et al, ), the relationship between inflammation and autophagy on AD development remains largely unclear.…”
Section: Discussionsupporting
confidence: 67%
“…Interestingly, it has recently been shown that autophagy negatively regulates inflammasome activation (reviewed in Pedraza‐Alva, Perez‐Martinez, Valdez‐Hernandez, Meza‐Sosa, & Ando‐Kuri, ), supporting previous observations indicating an inverse correlation between autophagy and inflammation in different pathological settings, affecting peripheral organs (Bianco, Girardelli, & Tommasini, ; Chang, Hee, Hsieh, Jeng, & Chuang, ; Lapaquette, Guzzo, Bretillon, & Bringer, ). Although, François et al, () reported that in the APPswe/PS1dE9 transgenic mice, inflammation could induce autophagy in older mice (François et al, ), the relationship between inflammation and autophagy on AD development remains largely unclear.…”
Section: Discussionsupporting
confidence: 67%
“…Therefore, a precise integration of both metabolic and inflammatory pathways is essential for the adaptations of hepatic metabolism to environment, but more generally for the regulation of whole-body metabolism. In agreement, mitochondrial dysfunction and ER stress have been largely and independently associated with metabolic diseases, such as obesity, type 2 diabetes mellitus (T2DM) (Chang et al 2015, Rieusset 2015, Salvado et al 2015, Hasnain et al 2016) and non-alcoholic fatty liver diseases (NAFLD) (Begriche et al 2013, Takaki et al 2014, Ashraf & Sheikh 2015. Moreover, the strong interplay between the two organelles and immune signaling (Hummasti & Hotamisligil 2010, Chaudhari et al 2014 further highlights their involvement in the progression toward metabolic diseases.…”
Section: Introductionmentioning
confidence: 89%
“…However, autophagy activity is greatly up-regulated in response to nutrient limitation or to an altered intracellular milieu. A dysregulation of autophagy activity contributes to the pathology of multiple diseases (Chang et al 2015;Tai et al 2016;Edens et al 2016), including complications of pregnancy (Hung et al 2012;Kanninen at el. 2013b;Gao et al 2015;Brickle et al 2015;Agrawal et al 2015).…”
mentioning
confidence: 99%